2019
DOI: 10.2147/ott.s221733
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-19a Is Involved In Progression And Malignancy Of Anaplastic Thyroid Cancer Cells</p>

Abstract: Background: MicroRNAs (miRNAs) are endogenous, single-stranded, non-coding RNAs acting as negative regulators of gene expression involved in a number of physiological processes. MiRNAs' expression is commonly dysregulated in many types of human tumor diseases and cancers, including thyroid cancers, and is often involved in tumor initiation and progression. miR-19a, a member of miR-17-92 cluster, has been demonstrated to promote cell growth in anaplastic thyroid cancer (ATC), the most advanced and aggressive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Recently, emerging studies have suggested that many other lncRNAs, such as PTCSC3 and HCP5, were dysregulated in ATC tissues and cells, implying that they might be promising biomarkers for ATC diagnosis [11,36]. Moreover, a group of miRNAs, including miR-19a and miR-483-3p, were reported to be involved in ATC progression, suggesting novel therapeutic targets for ATC treatment [37,38]. This study had led to a novel identification for the NEAT1/ miR-206 and NEAT1/miR-599 axis that might function as valuable diagnostic biomarkers and therapeutic targets for ATC management in further personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, emerging studies have suggested that many other lncRNAs, such as PTCSC3 and HCP5, were dysregulated in ATC tissues and cells, implying that they might be promising biomarkers for ATC diagnosis [11,36]. Moreover, a group of miRNAs, including miR-19a and miR-483-3p, were reported to be involved in ATC progression, suggesting novel therapeutic targets for ATC treatment [37,38]. This study had led to a novel identification for the NEAT1/ miR-206 and NEAT1/miR-599 axis that might function as valuable diagnostic biomarkers and therapeutic targets for ATC management in further personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miRNAs have been successfully demonstrated to be able to discriminate benign from malignant lesions in PTC (e.g., miRNA-221, miRNA-222, miRNA-181b, miRNA-146b) and FTC/HCC (e.g., miRNA 148b-3p, miRNA-484) and could be a guide to avoid unnecessary surgery [27,136,137]. Moreover, certain miRNAs were also identified in APC, such as miRNA-19a [26]. However, panels of miRNAs may have a higher sensitivity and specificity than single miRNA in distinguishing thyroid nodules [127,138].…”
Section: Mirna Markersmentioning
confidence: 99%
“…An example of evolving biomarkers for diagnosis and prognosis in TC are MicroRNAs (miRNA). By regulating target genes of various signalling pathways including gene expression of known oncogenes and tumour suppressor genes, they play a crucial role for cell differentiation, migration, invasion and even epithelial-to-mesenchymal transition (EMT) [26][27][28]. Furthermore, different and distinct miRNA profiles were identified in different TC subtypes [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, miR-205 expression could be used as potential option in order to halt or inhibit both angiogenesis and EMT in ATC. miR-19a is involved in the progression of ATC [38]. A significant reduction of cell proliferation was noticed in miR-19a downregulated ATC cells (8505c).…”
Section: Roles Of Mirnas In Anaplastic Thyroid Carcinomamentioning
confidence: 99%